Environmental education programmes offered by delta environmental centre: Some research findings - Doc Shongwe (Southern African Journal of Environmental Education, 1997)
Environmental education has developed over time in South Africa with environmental education centres playing a significant role. However not enough is known about how such centres operate. This article presents some of the findings of a research project that documented and evaluated the programmes presented by Delta Environmental Centre, in Gauteng, South Africa.